Opisanie nogo vida poda Poseidonemertes (Nemertea, Monostilifera) s obosnovaniem semeistva Poseidonemertidae [Description of a new species of the genus Poseidonemertes (Nemertea, Monostilifera) with establishment of the family Poseidonemertidae] - Chernyshev, A. V. (Zoologicheskii Zhurnal, 2002)
The new species, Poseidonemertes maslakovae sp. n. from the Peter the Great Bay (the Sea of Japan) is described. In this species, there are two eyes, the lateral pouches of intestinal caecum are absent, the lateral pouches of middle intestine are simple, cephalic glands are in front of the brain, the ratio of the central stylet length to that of the basis is 0.72-0.79, proboscis epithelium contains rabdit-like structures. The splitting of the anterior longitudinal musculature of the body wall and the corresponding transformation of the praecerebral septum are analyzed. The new terms - acclivous, longitudinal, and mixed praecerebral septum - are proposed. In the genera Poseidonemertes, Tetranemertes, Paramphiporus, Correanemertes, Alaxinus, Fasciculonemertes, Aenigmanemertes, Diopsonemertes, Kirsteueriella gen. n. (type species is Paranemertes biocellatus Coe) and also in "Paranemertes" californica Coe, the splitting of the longitudinal musculature is not related to the well developed cephalic glands. This group of genera N. is recognized to be monophiletic and is distinguished as the new family Poseidonemertidae.